Comparative study of the attributive effects of fresh and canned Naftussya water - Popovych, Andriy; Fil, Vitaliy; Ruzhylo, Sofiya; Zakalyak, Nataliya; Żukow, Xawery; Popovych, Dariya (Journal of Education, Health and Sport, 2023)
Background. There are several patented methods of preservation of medicinal waters of the Naftussya type. The authors of the patents as evidence of the correctness of the methods cite the facts of preservation of the ability of canned water to enhance motility rat’s v. portae in vitro and/or increase diuresis. However, such tests are not attributive. The most characteristic manifestation of the biological activity of Naftussya water is the stimulation of phagocytosis. Another "Method of preservation of hydrogen sulfide mineral waters" was recently patented. Based on the above, we will use attributive tests for its verification. Materials and Methods. The object of clinical-physiological observation were residents of the city of Truskavets’ (21 men aged 24-67 years and 8 women 33-76 years) with chronic pyelonephritis in remission. The subject of the study were the phagocytic function of neutrophils, excretory function of kidneys as well as leukocyturia and bacteriuria levels and components of microbiota of feces. Results. Weekly use of fresh Naftussya water causes an increase in the reduced content of probiotics in the microbiota and a decrease in the increased content of conditionally pathogenic microflora, which is accompanied by an increase in reduced bactericidal capacity of neutrophils against both E. coli and Staph. aureus, normal diuresis, phosphaturia, magnesiumuria, ureauria while reduction of bacteriuria and leveling of leukocyturia as well as decrease in concentration of uric acid in urine and creatinine and cholesterol in plasma. The beneficial effect on the listed parameters of canned Naftussya water is less pronounced, but the differences are statistically insignificant. Conclusion. The obtained results confirm the effectiveness of the Dovzhenko© method for Naftusya water conservation and provide grounds for continuing research into the effects of canned Naftusya water on the body of urological patients.